TEAMS GAMES TOURNAMENT SEBAGAI UPAYA PENINGKATAN KEMAMPUAN BELAJAR PADA MATA KULIAH AKUNTANSI BIAYA - Khafid, Muhammad (Dinamika Pendidikan, 2010)
The purposes of this study are to (1) test and gain empirical evidence on the effectivity of Teams Games Tournament as a teaching method used in Cost Accounting I to improve studentsâ competence on group work; (2) test and gain empirical evidence on the advantages of Teams Games Tournament as a teaching method in Cost Accounting I to improve studentsâ comprehension and active involvement in teaching-learning process. The subject of the study wasÂ  Accounting students on 4th semester of Semarang State University who were taking Cost Accounting I. This study involved 2 lecturers who also taught Cost Accounting I. Â Data collection methods were documentation, test, and observation. This research was conducted in three cycles. Each cycle consisted of several stages; they were pre-reflection, planning, acting, observation and post-reflection. The result showed that teaching Cost Accounting I by implementing Teams Games Tournament Â as a Teaching Method on raw material cost, labor cost, and factory overhead cost can improve studentsâ competence and active involvement in teaching-learning process. It is proven that average scores of 10 teams of 1st, 2nd and 3rd Cycles were getting better; the scores were 61,07; 70,57; and 89,07. It indicates that the result has reached the stated target that is if students who get score more than 70 were 80% or more, the teaching method is considered successful. Therefore, it is necessary to conduct further research to find out the effectivity of Teams Games Tournament as a teaching method in other accounting subjects by modifying the research design in order to get significant changes.